Multimodal imaging and photothermal synergistic immunotherapy of retinoblastoma with tuftsin-loaded carbonized MOF nanoparticles - Hongmi Zou; Meng Li; Xing Li; Wendi Zheng; Hongyu Kuang; Menglei Wang; Wenli Zhang; Haitao Ran; Huafeng Ma; Xiyuan Zhou (Drug Delivery, 2022)
Retinoblastoma (Rb) represents 3% of all childhood malignancies and seriously endangers children's lives and quality of life. Early diagnosis and treatment can save children's vision as much as possible. Multifunctional nanoparticles have become a research hotspot in recent years and are expected to realize the integration of early diagnosis and early treatment. Therefore, we report a nanoparticle with dual-mode imaging, photothermal therapy, and immune activation: carbonized MOF nanoparticles (CM NPs) loaded with the immune polypeptide tuftsin (CMT NPs). The dual-mode imaging ability, antitumor effect, and macrophage immunity activation ability of these nanoparticles combined with laser irradiation were studied. The biosafety of CMT NPs was detected. The multifunctional magnetic nanoparticles enhanced photoacoustic (PA) and magnetic resonance (MR) imaging in vivo and in vitro, facilitating diagnosis and efficacy evaluation. The combined effect of CMT NPs and laser irradiation was recorded and verified. Through the accumulation of magnetic field nanoparticles in tumors, the photothermal conversion of nanoparticles under laser irradiation led directly to tumor apoptosis/necrosis, and the release of tuftsin induced macrophage M1-type activation, resulting in antitumor immune effects. Enhanced PA/MR imaging CMT NPs have great potential in dual-mode image-guided laser/immune cotherapy. The nanoparticles have high biosafety and have potential in cancer treatment.